The Effectiveness of Agentic Group Guidance Services to Improve Self-Control of Minangkabau Ethnic Youth - Afifah Afifah; Herman Nirwana; Yeni Karneli; Rezki Hariko; Syuryani Syuryani (Jurnal Penelitian Pendidikan IPA, 2025)
During adolescence, individuals spend more time in social life outside the home, such as socializing with peers and socializing at school and in the community. Self-control is the ability of adolescents to control themselves. If self-control is successfully improved, then the self-control is high. Conversely, low self-control indicates that they are less able to control themselves. This study aims to test the effectiveness of agentic group guidance to improve self-control of Minangkabau ethnic adolescents. This study is a quantitative study with a quasi-experimental method with a Nonequivalent Control Group Design on 22 students of SMA Negeri 1 Batipuh who were divided into experimental and control groups. The research instrument was a Likert scale self-control questionnaire, analyzed using the N-Gain, Wilcoxon, and Mann Whitney tests. The results showed that the average pretest score of the experimental group was 131.63 increased to 154.38 in the posttest, with an N-Gain of 58.05 (quite effective category). Meanwhile, the control group increased from 124.91 to 158.18, with an N-Gain of 46.91 (less effective category). The Mann Whitney test produced Z = -2.66 and Sig. = 0.008 (< 0.05), indicating that there is a significant difference between the two groups.